Antarktis - kort fortalt - Balto, Ann Kristin; Hallanger, Ingeborg Gammelsæter; Jenssen, Elin Vinje (Norsk polarinstitutt, 2015)
Keywords: Antarktis; biologi; fauna; flora; historie; klima; miljø; natureklima; naturhistorie

Mapping lichen distribution on the Antarctic Peninsula using remote sensing, lichen spectra and photographic documentation by citizen scientists - Casanovas, Paula; Black, Martin; Fretwell, Peter; Convey, Peter (Polar Research, 2015)
On the Antarctic Peninsula, lichens are the most diverse botanical component of the terrestrial ecosystem. However, detailed information on the distribution of lichens on the Antarctic Peninsula region is scarce, and the data available exhibit significant heterogeneity in sampling frequency and effort. Satellite remote sensing, in particular the use of the Normalized Difference Vegetation Index (NDVI), has facilitated determination of vegetation richness and cover distribution in some remote and otherwise inaccessible environments. However, it is known that using NDVI for the detection of vegetation can overlook the presence of lichens even if their land cover is extensive. We tested the use of known spectra of lichens in a matched filtering technique for the detection and mapping of lichen-covered land from remote sensing imagery on the Antarctic Peninsula, using data on lichen presence collected by citizen scientists and other non-specialists as ground truthing. Our results confirm that the use of this approach allows for the detection of lichen flora on the Antarctic Peninsula, showing an improvement over the use of NDVI alone for the mapping of flora in this area. Keywords: Antarctica; NDVI; matched filtering; Landsat; remote sensing.
Keywords: Antarktis; botanikk; flora; lav; satellitt bilder; økosystemer

Methane and nitrous oxide fluxes in relation to vegetation covers and bird activity in ice-free soils of Rip Point, Nelson Island, Antarctica - Neufeld, Ângela Denise Hubert; de Godoi, Stefânia Guedes; Pereira, Antônio Batista; Bayer, Cimélio; Schünemann, Andriano Luis; de Carvalho Victoria, Filipe; de Albuquerque, Margéli Pereira; Camargo, Estefânia; Vieira, Frederico Costa Beber (Polar Research, 2015)
This study aimed to quantify the nitrous oxide (N2O) and methane (CH4) fluxes at sites with different vegetation covers and where bird activity was present or absent using the static chamber method, on Rip Point, Nelson Island, maritime Antarctic. The sites were soils covered by Sanionia uncinata, lichens, Prasiola crispa, Deschampsia antarctica and bare soil. Seabirds used the P. crispa and D. antarctica sites as nesting areas. Soil mineral N contents, air and soil temperature and water-filled pore space were measured, and the content of total organic C and particulate organic C, total N, bulk density and texture were determined to identify controlling variables of the gas emissions. The N2O and CH4 flux rates were low for all sampling events. Mean N2O flux rates ranged from 0.11±1.93 up to 21.25±22.14 µg N2O m−2 h−1 for the soils under lichen and P. crispa cover, respectively. For the CH4 fluxes, only the P. crispa site showed a low positive mean (0.47±3.61 µg CH4 m−2 h−1). The bare soil showed the greatest absorption of CH4 (−11.92±5.7 µg CH4 m−2 h−1), probably favoured by the coarse soil texture. Bare soil and S. uncinata sites had N2O accumulated emissions close to zero. Net CH4 accumulated emission was observed only at the P. crispa site, which was correlated with (p<0.001). These results indicate that seabird activity influences N2O and CH4 soil fluxes, while vegetation has little influence, and bare soil areas in maritime Antarctica could be greenhouse gas sinks. Keywords: Soil greenhouse gases; seabirds; vegetal cover; maritime Antarctica.
Keywords: Antarktis; biogeokjemi; drivhuseffekt; drivhusgasser; flora; global oppvarming; klimaendringer; klimagasser; planter; sjøfugler; økosystemer